Description of three novel species of Scandinavium: Scandinavium hiltneri sp. nov., Scandinavium manionii sp. nov. and Scandinavium tedordense sp. nov., isolated from the oak rhizosphere and bleeding cankers of broadleaf hosts - Daniel Maddock; Helene Kile; Sandra Denman; Dawn Arnold; Carrie Brady (Frontiers in Microbiology, 2022)
While investigating the bacterial populations of environmental samples taken from a mix of healthy and Acute Oak Decline afflicted Quercus robur (pedunculate or English oak) rhizosphere soil samples and swabs of bleeding lesions on Tilia spp. (lime) and Quercus rubra (red oak) trees, several strains belonging to the order Enterobacterales were isolated using selective media and enrichment broth. Seven strains from the Q. robur rhizosphere, three strains from Tilia spp. and one from Q. rubra were investigated, with their taxonomic status determined via a polyphasic taxonomic approach. Initially stains were identified as potential members of the recently described genus Scandinavium, based on the partial sequencing of three housekeeping genes. Further analysis of phenotypic traits, including fatty acid profiles, coupled with 16S rRNA gene and phylogenomic analysis of whole genome sequences were applied to a subset of the strains. Phylogenetic and phylogenomic analysis repeatedly placed the isolates in a monophyletic clade within Scandinavium, with four distinct clusters observed, one of which corresponded to Scandinavium goeteborgense, the type species of the genus. The remaining three clusters could be phenotypically and genotypically differentiated from each other and S. goeteborgense. As such, we describe three novel species of the genus, for which we propose the names Scandinavium hiltneri sp. nov. (type strain H11S7T = LMG 32612T = CCUG 76179T), Scandinavium manionii sp. nov. (type strain H17S15T = LMG 32613T = CCUG 76183T) and Scandinavium tedordense sp. nov. (type strain TWS1aT = LMG 32614T = CCUG 76188T). Additionally, the descriptions of the genus Scandinavium and the type species, S. goeteborgense, are emended.